2005
DOI: 10.1111/j.1365-2044.2004.04111.x
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical embolism through a patent foramen ovale: an unexpected complication of tracheal extubation

Abstract: A 41-year-old male with insulin-dependent diabetes mellitus was admitted for an elective arthroscopic release of adhesive capsulitis of his left shoulder. At the end of the surgical procedure, he appeared to regain consciousness but then became unresponsive at the time of tracheal extubation after a violent bout of coughing, developing bilateral up-going plantar responses, decorticate posturing and abnormal pupillary reflexes. He was transferred to the intensive care unit. The following day, the patient made a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…We suspect in retrospect that the patient's initial presentation with status epilepticus was caused by cerebral air embolism that was missed clinically and by the initial head CT. Cerebral air embolism may not be well visualized on CT [1]. Reported causes of cerebral air embolism include cardiopulmonary bypass [2], endoscopic retrograde cholangiopancreatography [3], central venous catheter manipulation [4,5], contrast-enhanced computed tomography [6], radial artery catheterization [7], cardiopulmonary resuscitation [8], tracheal extubation [9], inadvert aircraft Non-contrast head CT shows massive intravascular air (white arrows) with diffuse cerebral edema and loss of gray-white matter differentiation (b, c) depressurization [10], cardiac ablation procedures [11], high frequency oscillatory ventilation [12], and cerebral and coronary angiography [13], [14]. None of these procedures or events preceded this patient's symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…We suspect in retrospect that the patient's initial presentation with status epilepticus was caused by cerebral air embolism that was missed clinically and by the initial head CT. Cerebral air embolism may not be well visualized on CT [1]. Reported causes of cerebral air embolism include cardiopulmonary bypass [2], endoscopic retrograde cholangiopancreatography [3], central venous catheter manipulation [4,5], contrast-enhanced computed tomography [6], radial artery catheterization [7], cardiopulmonary resuscitation [8], tracheal extubation [9], inadvert aircraft Non-contrast head CT shows massive intravascular air (white arrows) with diffuse cerebral edema and loss of gray-white matter differentiation (b, c) depressurization [10], cardiac ablation procedures [11], high frequency oscillatory ventilation [12], and cerebral and coronary angiography [13], [14]. None of these procedures or events preceded this patient's symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence from TOE and bubble studies has shown that there is an increased risk of paradoxical embolism using femoral venous access due to the preferential direction of the inferior vena cava flow towards the inter-atrial septum, as compared to the superior vena cava. [6] Autopsy reports suggest that PFOs occur in 11-35% of the normal population, and are predominately a silent, innocent Paradoxical embolus during lead extraction phenomenon. [3] They can, however, be a source of paradoxical embolism, resulting in varied negative sequelae including cryptogenic stroke, peripheral embolism, brain abscess and decompression illness.…”
Section: Discussionmentioning
confidence: 99%
“…6 In a review of all patients in the literature with cerebral air embolism associated with CVCs from 1975 to 1988, 54% occurred secondary to disconnection of CVCs, 31% occurred during removal of CVCs, and 15% occurred during insertion. 9 Other reported causes of cerebral air embolism include cardiopulmonary bypass, 10 intrathoracic anticancer drug administration, 11 endoscopic retrograde cholangiopancreatography, 12,13 contrast-enhanced computed tomography (CT), 14 CT-guided lung biopsy, 15 compressed air diving, 16 intra-aortic balloon pump rupture, 17 radial artery catheterization, 18,19 cardiopulmonary resuscitation, 20 tracheal extubation, 21 upper endoscopy, 22 endoscopic variceal ligation, 23 inadvertent aircraft depressurization, 24 diagnostic bronchoscopy, 25 transbronchial biopsy, 26,27 lung contusion, 28 inactive tuberculosis cavity, 29 esophageal carcinoma, 30 inhalation of pressurized helium, 31 pleurodesis, 32 cardiac ablation procedures, 33 and cerebral angiography. 34 Symptoms of venous air embolism (VAE) are referable to its effects on gas exchange and central hemodynamics.…”
Section: Discussionmentioning
confidence: 99%